Potentially harmful cyanobacteria in oyster banks of Términos lagoon, southeastern Gulf of Mexico (2018)
Cyanobacteria inhabit hypersaline, marine and freshwater environments. Some toxic and non-toxic species can form harmful blooms. The aim of this study was to identify potentially harmful cyanobacterial species in the oyster banks of Términos Lagoon, the southeastern Gulf of Mexico. Six sample sites (up to 2-m depth) were monitored monthly from August 2012 to September 2013. Water temperature, salinity, pH, dissolved oxygen saturation (% DO), inorganic nutrients and abundance of cyanobacteria were determined. Temperature and salinity were characterized by marked seasonal differences (26.8 to 30.6 °C and 6.1 to 19.5, respectively). The pH values (ranging from 7.1 to 8.4) and the % DO (88.4 to 118.2 %) suggest a predominance of photosynthetic activity in the windy season (October-February). Elevated nutrient contents are associated with the period of increased river discharge, determined by water circulation and biogeochemical processes. Fourteen taxa were identified, of which Anabaena sp., Merismopedia sp., Oscillatoria sp. and Cylindrospermopsis cuspis produced blooms. Cyanobacterial abundances were on the order of magnitude of 106 cells L-1 in October 2012 at stations S1-S6, with an average value of 3.2x105 cells L-1 and a range of 2000 to 3.1x106 cells L-1 throughout the study period; however, they showed a remarkable absence during the windy season (October to January). Anabaena sp. and C. cuspis reached abundances of 1.9x106 and 1.3x106 cells L-1, respectively. The latter caused the temporary closure of oyster Crassostrea virginica harvesting for 15 days in October 2012.